A Novel GS1 Data Standard Adoption Roadmap for Healthcare Providers (2011)
The use of GS1 Data Standards is envisioned to improve the efficiency of the healthcare supply chain as it did for the retail supply chain. The healthcare industry, especially providers, acknowledges their potentials; however, there are misconceptions and lack of understanding the associated costs and expected benefits. This study presents an adoption roadmap for GS1 Data Standards at the provider level in healthcare industry. The developed roadmap is a result of systematic efforts at conducting extensive studies, examining the best practices, and interacting with industry leaders. The adoption roadmap includes different levels and sublevels to provide a flexible foundation for healthcare providers where alternative adoption paths will be available for their immediate needs and requirements. Sublevels have a recommended precedence structure to realize maximum gains from the adoptions. The feasibility and practicality of the developed roadmap has been validated by two pilot studies, which were conducted in collaboration with two hospital provider partners. The pilot studies helped identify potential benefits as well as roadblocks and barriers for different levels of GS1 Data Standards adoption. The results indicate that the adoption is not an easy process and may require many workarounds; however, the potential gains are significant.